Stability in stem population in Urochloa cultivars with different cutting intensity: Intensidad y estabilidad de tallos - Lucio-Ruiz, Fernando; Garay-Martínez, Jonathan R.; Bautista-Martínez, Yuridia; Estrada-Drouaillet, Benigno; Hernández-Guzmán, Filogonio J.; Limas-Martínez, Andrés G.; Joaquín-Cancino, Santiago (Ecosistemas y Recursos Agropecuarios, 2021)
With the objective of determine the effect of cutting intensity on the population stability of stems in cultivars of the genus Urochloa (hybrids Mulato II, Cayman and Xaraés), using a completely randomized design with factorial arrangement (3 × 2 × 11); where the first factor was the Urochloa cultivars (Mulato II, Cayman and Xaraés), the second the intensity levels (fixed and 50%) and 8 sampling dates (every four weeks). The experimental unit was an area of ​​100 cm2 where each generation (sampling date) was marked with rings of different colors to distinguish them. A completely randomized design with six repetitions per intensity was used in each cultivar. The highest population density of stems was presented in the fixed intensity with 2333.66, 2500.77 and 2119.59 stems m-2, a result of the balance between the rate of appearance and death, obtaining survival rates between 89.18 and 92.45 % and stability indices greater than 0.95 and less than 1.05, that is, the fixed cutting intensity of 15 cm for Mulato II and Cayman and 20 cm for Xaraés favors the stability of the meadow, increasing persistence over time.